Enforcement of The Advocate Code of Ethics in Cases of Contempt of Court in Indonesia - MARTHA, I Dewa Agung Gede Mahardhika (Journal of Tourism Economics and Policy, 2025)
The legal profession plays a crucial role in upholding justice and judicial authority. Advocates, as independent law enforcers, are bound by ethical standards governing their conduct in court. This study examines the enforcement of advocates' codes of ethics in Indonesia in contempt of court cases, focusing on the adequacy of the legal framework, the effectiveness of ethical sanctions, and implementation challenges through a normative legal approach supported by empirical data. The findings indicate that although Indonesia possesses a comprehensive normative basis through Law Number 18 of 2003 on Advocates, the Advocates' Code of Ethics, and provisions of the Criminal Code, the enforcement of ethical norms remains suboptimal in practice. Key obstacles include weak internal supervision mechanisms, fragmentation of advocate organizations, lack of transparency in ethical proceedings, conflicts of interest within disciplinary bodies, and the absence of clear guidelines distinguishing legitimate legal criticism from contempt of court. The case of advocate Firdaus Oiwobo illustrates the inconsistencies and delays in ethical enforcement, which ultimately undermine public trust in the legal profession. This study concludes that reforms are urgently needed, including the establishment of an independent and integrated ethical oversight body, the formulation of clear technical guidelines on contempt of court, and the strengthening of continuous legal ethics education. Such measures are essential to preserve the dignity of the legal profession, ensure legal certainty, and reinforce judicial authority in line with the principles of the rule of law.